Identifying relevant factors for successful implementation into routine practice: expert interviews to inform a heart failure self-care intervention (ACHIEVE study) - Oliver Rudolf Herber; Isabell Ehringfeld; Paula Steinhoff; Amanda Whittal (BMC, 2021)
Abstract Background Adherence to heart failure (HF) self-care behaviours has been found to be effective for alleviating illness symptoms, increasing quality of life and reducing hospital re-admissions and mortality. However, many patients fail to implement on-going self-care into their daily lives. It is therefore crucial to improve the behaviour of HF patients to increase self-care adherence. The aim of this study is to identify relevant factors to successfully implement a complex, theory-based HF self-care intervention into routine practice. Methods We conducted semi-structured interviews to obtain key stakeholders' opinions on previously developed behaviour change techniques for enhancing HF patients' self-care behaviours, in order to optimise implementation of these techniques in an intervention. The interview topic guide was developed based on the Normalisation Process Theory (NPT), a tool that takes into account the feasibility of implementation and the acceptability to stakeholders. Interviews were analysed using thematic analysis and supported by MAXQDA 2020, a software for qualitative research. Results Interview participants included 18 key stakeholders consisting of three crucial groups: clinical experts (n = 7), patients (n = 3) and high calibre policy makers/potential funders (n = 8). The interviews revealed numerous factors to consider for successful implementation of an intervention into routine practice. The findings are presented according to two major categories: (1) themes within the NPT framework and (2) themes beyond the NPT framework. Themes within the NPT component 'Coherence' include three sub-themes: 'understandability', 'value beyond existing interventions' and 'perceived benefits'. The NPT component 'Cognitive participation' revealed two sub-themes: 'time resources' and 'financial sustainability'. Finally, the NPT component 'Collective action' uncovered three sub-themes: 'need for training', 'compatibility with existing practice' and 'influence on roles'. A further two themes were identified beyond the NPT framework, namely: 'structural challenges' and (2) 'role of carers'. Conclusions Factors identified previously by NPT were validated, but stakeholders further identified relevant aspects beyond NPT. Based on these findings, we suggest the existing NPT framework could be expanded to include a fifth component: questions considering specific environmental factors (contextual considerations). Sensitising researchers to these issues at an early stage when designing an intervention can facilitate its later success.